Thomas & friends : Stafford mogok / W. Awdry; Penerjemah, Ayu Prameswary; Editor, Putri Fitrisia dan Tessa Febriani - AWDRY, W.; AYU Prameswary; PUTRI Fitrisia; TESSA Febriani (Erlangga, 2013)
24 hlm. : Ilus. ; 23 cm.